2015
DOI: 10.1007/s11999-014-3769-5
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Mental Health in Primary Total Knee Arthroplasty?

Abstract: Background Psychological distress has been associated with inferior scores for pain after total knee arthroplasty (TKA). However, its relationships with scores and arthrofibrosis after TKA remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Depression has been linked to an increased fall rate after TKA [26], which certainly predisposes to increased periprosthetic fracture, patellar complications, and extensor mechanism rupture. Furthermore, patients with arthrofibrosis and psychological distress perceived themselves as having worse knee scores and overall health, but the rate of MUA was not evaluated [27]. Pfefferle and colleagues utilized the Explorys software to mine national healthcare databases and found that depression was not associated with an increase in MUA [28], similar to the findings in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Depression has been linked to an increased fall rate after TKA [26], which certainly predisposes to increased periprosthetic fracture, patellar complications, and extensor mechanism rupture. Furthermore, patients with arthrofibrosis and psychological distress perceived themselves as having worse knee scores and overall health, but the rate of MUA was not evaluated [27]. Pfefferle and colleagues utilized the Explorys software to mine national healthcare databases and found that depression was not associated with an increase in MUA [28], similar to the findings in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Satisfaction is based not just on physical gains or limitations, but is strongly affected by the patient's psychological state amongst other factors. [25][26][27] The development of more sophisticated outcome measures may allow more accurate assessment of satisfaction in patients undergoing TKR.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of anxiety and depression adversely affect outcomes scores in patients whose physical health status is objectively no worse [12,15]. While those symptoms can confound the use of otherwise valid patient-reported outcomes tools, they render the measurement of satisfaction with treatment outcomes all but impossible.…”
mentioning
confidence: 99%